Conoscenza dell’istinto di morte. Due presentazioni - Vari, Autori (Il sogno della farfalla, 2019)
This article collects two presentations from the volume Conoscenza dell’istinto di morte by Massimo Fagioli, which took place in Rome and Milan respectively on 24th September and 19th November 2017. Published few months after the passing of the Collective Analysis psychiatrist, the book presents the psychology lectures held by the author at the University of Chieti-Pescara “G. d’Annunzio” in 2012. The presentations analyse some of the most important themes covered during the lessons in which the author discusses his fundamental discoveries on the human birth dynamic. The speakers particularly focus on the author’s human and scientific research and their own personal and direct experience of his theory and practice.